Production Of Ready-To-Drink Cascara Kombucha Fortified With Coconut Water (Cocos Nucifera L.) and Red Dragon Fruit (Hylocereus Polyrhizus) - Taufik, Refika Safitri Rizkia; Zackiyah, Zackiyah; Supriyanti, Florentina Maria Titin (Jurnal Natural Scientiae, 2024)
Cascara is coffee pulp which contains caffeine, chlorogenic acid and phenolic compounds, but has not been utilised optimally. Cascara can be processed into ready-to-drink cascara kombucha products, which are beneficial for the body. This research aims to determine the effect of adding coconut water (Cocos nucifera L.) and red dragon fruit (Hylocereus polyrhizus) on the alcohol content, total phenolics, caffeine, minerals, antioxidant activity and sensory hedonic content of ready-to-drink cascara kombucha. This research method was carried out in 3 stages including optimizing fermentation time and SCOBY starter concentration based on pH value; fortification ratio optimization; and product analysis includes alcohol content by dichromate method, total phenolics by Folin-Ciocalteu method, caffeine by UV-VIS spectrophotometry method, minerals by AAS spectrophotometry method, antioxidant activity by DPPH method, and sensory hedonic. The research results showed that the best time was 12 days, pH value 3.42 at 10% SCOBY starter concentration. The ratio of cascara kombucha : fortificant is 1:1 resulting in an alcohol content of 0.23-0.43%. The highest levels for total phenolics, caffeine, and minerals were 656.32 mg/kg; 35.53 ppm; and 732.83 mg/100g respectively. The highest antioxidant activity was obtained from the red dragon fruit fortified cascara kombucha product with a yield of 89.69%. The highest color and aroma attributes were obtained from the cascara kombucha product fortified with a mixture of coconut water and red dragon fruit, while the highest value for the taste attribute was obtained from the cascara kombucha product fortified with red dragon fruit.